Upaya BRICS Dalam Mengimbangi Dominasi Dolar AS - Alfiyah, Nur Inna; Andrianingsih, Very; Laras Asih, Dessy Novitasari; Ainun, Moh. Baqir (Journal MISSY (Management and Business Strategy), 2024)
Dependence on the use of the US dollar in the world economy often harms developing countries with fiscal policies and the imposition of economic sanctions imposed by the US, making the economic position of developing countries vulnerable. So BRICS was born to bridge the global economic needs of developing countries, as an effort to balance of power in the world economy. This research aims to determine BRICS' efforts to offset the dominance of the use of the US dollar which is explained using qualitative descriptive methods. The effort to create a balance of power in the economy carried out by BRICS is by issuing BRICS currency which can have an impact on the use of dollars in trade transactions between BRICS member countries. Trade transactions carried out by BRICS member countries increase every year even without using the dollar as a transaction tool. So, to make the global success of the use of the BRICS currency, cooperation and collaboration between member countries is needed to be able to influence non-BRICS member countries to join in using the BRICS currency in their international economic and trade transactions.